Dr. Charles David Herrold. - Gordon, John C. (photographer):::Creator::::::::::::
Written on verso: "Prof. Phil Hoerald [sic] gather at radio-Radio H.O.W.; Baptist Church San Jose." Professor Charles D. Herrold founded the World's first radio broadcasting station in 1909. This station came into existence in the laboratory of Herrold's College of Engineering & Wireless, located in San Jose's Garden City Bank Building on the southwest corner of First and San Fernando Streets.